ZAKAT PROFESI DALAM PERSPEKTIF UU RI NOMOR 23 TAHUN 2011 DAN HUKUM ISLAM - Aziz, Muhammad; Sholikah, Sholikah (ULUL ALBAB Jurnal Studi Islam, 2014)
One of the real object of charity to this day is still debatable zakat profession, although its existence is still debated, but many have been put into practice, including the case that the rule in Indonesia, who wants to know in this article are; how the zakat profession in the legal perspective number 23 year 2011 about the management of zakat and Islamic law? This paper uses qualitative research methods to the study of comparative - descriptive - analytic, ie describe the Surah al-Baqarah: 167, hadith of the Prophet narrated by Said bin Abi Burdah, and scholars' opinions, as well as Law No. 23 of 2011, in particular article that talk about charity profession, comparing expert opinion in fiqh, then analyze it critically. This paper concludes; Zakat Law No. profession in perspective. 23 in 2011, to emphasize that the charity has an official and legal profession institutionalized in formal, binding and juridical in the regulation of the state of Indonesia. existence of zakat profession in this regulation, as well as to provide legal certainty on the Muslim individual and business entity owned by Muslims in zakat to mustahiq transfer can also be used as part of Islamic philanthropy that can be used for the welfare of Muslims, the case so this is also part of the basic management of zakat perpspektif Law No. 23 year 2011 is. Zakat profession in Islamic law perspective to emphasize that the obligation of zakat profession based on letters of al -Baqarah: 267 of a general nature, hadiths of a general nature and analyzes of Islamic jurists (fuqaha') good classic or contemporary. The case has implications regarding the result of the material, whether derived from trade, capital investment, honorarium, salary, etc., or even in terms of the time limit should not have been in possession of the property.